Mullite-reinforced caprolactam-toughened DGEBA epoxy nanocomposites: Preparation and characterization. (November 2015) - Kanimozhi, K.; Prabunathan, P.; Selvaraj, V.; Alagar, M.
This work describes the development of different weight percentages of glycidyl functionalized mullite-reinforced caprolactam-toughened epoxy (MCEP) nanocomposites. The functionalization of mullite and MCEP are confirmed by Fourier transform infrared spectroscopic analysis. Further, the morphological, surface behaviour and thermal properties are studied using scanning electron microscopy, transmission electron microscopy, X-ray diffraction, atomic force microscopy, goniometer, thermogravimetric analysis and differential scanning calorimetry analysis. Surface studies show that the values of contact angle increased with increase in weight percentage of mullite and thus 1.5 wt% MCEP nanocomposites show values of higher contact angle (89.6°) and lower water absorption (0.107%) behaviour than those of the composites reinforced with lower wt% of mullite. Moreover, 1.5 wt% MCEP nanocomposites possess better impact behaviour (266.4 J m −2 ) than that of neat epoxy matrix. Thus the hybrid composite materials developed in this work are expected to find applications in different industrial and engineering sectors with improved performance and longevity.